Respuesta :

Answer:

[tex]f(g(5)) = 5[/tex]

[tex]g(f(4)) = 0[/tex]

[tex]f(f(6))=1[/tex]

[tex]g(g(9)) = 0[/tex]

Step-by-step explanation:

Given

The attached table of values

Solving (a): f(g(5))

First, we solve for g(5)

[tex]g(5) = 7[/tex]

So:

[tex]f(g(5)) = f(7)[/tex]

Next, we solve for f(7).

From the table

[tex]f(7) = 5[/tex]

So:

[tex]f(g(5)) = 5[/tex]

Solving (b): g(f(4))

First, we solve for f(4)

[tex]f(4) = 6[/tex]

So:

[tex]g(f(4)) = g(6)[/tex]

Next, we solve for g(6).

From the table

[tex]g(6) = 0[/tex]

So:

[tex]g(f(4)) = 0[/tex]

Solving (c): f(f(6))

First, we solve for f(6)

[tex]f(6) = 8[/tex]

So:

[tex]f(f(6)) = f(8)[/tex]

Next, we solve for f(8).

From the table

[tex]f(8) = 1[/tex]

So:

[tex]f(f(6))=1[/tex]

Solving (d): g(g(9))

First, we solve for g(9)

[tex]g(9) = 6[/tex]

So:

[tex]g(g(9)) = g(6)[/tex]

Next, we solve for g(6).

From the table

[tex]g(6) = 0[/tex]

So:

[tex]g(g(9)) = 0[/tex]